1997
DOI: 10.3109/00207459709000637
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Electromagnetic Fields Reverses the Long-Term Clinical Course of a Patient with Chronic Progressive Multiple Sclerosis

Abstract: It is estimated that 10-20% of patients with multiple sclerosis (MS) have a chronic progressive (CP) course characterized by an insidious onset of neurological deficits followed by steady progression of disability in the absence of symptomatic remission. To date no therapeutic modality has proven effective in reversing the clinical course of CP MS although there are indications that prolonged treatment with picotesla electromagnetic fields (EMFs) alters the clinical course of patients with CP MS. A 40 year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Since obtaining approval from the United States Food and Drug Administration in 1979, pulsed electromagnetic therapy (PEMT) has been widely used to counteract pain resulting from various conditions such as arthritis of the knee joint, 1 -3 ligament and muscle injuries, 1,4,5 delayed union fracture, 6 whiplash injury, 7 chronic pelvic pain, 8 headache, 9 complex regional pain syndrome type I 10 and multiple sclerosis. 11 In addition, PEMT has also been used to prevent osteoporosis 12,13 and enhance scar healing. 14,15 However, its efficacy and the optimal modes of magnetic field administration remain intensely controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Since obtaining approval from the United States Food and Drug Administration in 1979, pulsed electromagnetic therapy (PEMT) has been widely used to counteract pain resulting from various conditions such as arthritis of the knee joint, 1 -3 ligament and muscle injuries, 1,4,5 delayed union fracture, 6 whiplash injury, 7 chronic pelvic pain, 8 headache, 9 complex regional pain syndrome type I 10 and multiple sclerosis. 11 In addition, PEMT has also been used to prevent osteoporosis 12,13 and enhance scar healing. 14,15 However, its efficacy and the optimal modes of magnetic field administration remain intensely controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetostimulation reduces the symptoms of depression, improves the mood of patients, reduce anxiety. The results of clinical trials confirmed the high therapeutic efficacy of magneto-stimulation using weak variable magnetic fields in the treatment of neurotic symptoms in the course of multiple sclerosis, Parkinson's disease and Alzheimer's disease [46]- [49]. In the paper [50], the authors described positive effects of treatment with EMFs of a patient with chronic progressive MS.…”
Section: Magnetostimulationmentioning
confidence: 74%
“…enkephalin, endorphin) and pain behavioral actions in various species including humans (11,12,14,15,17). Clinically, EMFs has shown some benefits in patients with joint diseases, pelvic pain and neurological disorders such as epilepsy, multiple sclerosis, and Parkinson's disease (1,2,5–7). The results in this study suggested that EMFs at appropriate parameters might be effective in reducing cardiac pain.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have shown that electromagnetic field stimulation (EMFs) provides different levels of pain relief in patients with some diseases and neuromuscular disorders (1)(2)(3)(4)(5)(6)(7). Also, this technique has been used in the treatment of various neurological disorders such as multiple sclerosis, epilepsy and Parkinson's disease (1,5,6).…”
Section: Introductionmentioning
confidence: 99%